THE EXTRACTION OF NICKEL(II) AND COPPER(II) USING LIQUID MEMBRANE EMULSION TECHNIQUE - Pirim Setiarso; Selvi Purwanti N. (Indonesian Journal of Chemistry, 2006)
Research on the extraction of Nickel(II) and Copper(II) using liquid membrane emulsion technique has been conducted. The purpose of this research is to know the influence of pH, extraction time and presence of competed metals (Ni2+ in Cu2+ and vice versa) toward the membrane extraction capability. In this research, 84 mL of Ni2+ and Cu2+ with concentration of 100 ppm, each, was extracted using pH variation (4.0, 4.5, 5.0, 5.5, 6.0). The optimum pH will be used to obtain the time of equilibrium and influence of the competed ions. Time variations (15, 20, 25, 30, 35 minute) were used with the concentration of the competed ions of 20, 40, 60, 80, 100 ppm. The percentage of ions extracted was analyzed by Atomic Absorption Spectrometry. The result shows that the optimum pH was 5.0 for extracting 79.3137 % Cu2+ and 50.3448 % Ni2+. Time of equilibrium was 30 minutes for extracting  85.4117 % Cu2+ and 53.7691 % Ni2+. The presence of Ni2+ influenced Cu2+ extracted and vice versa.